Melanoma patients with immune-related adverse events after immune checkpoint inhibitors are characterized by a distinct immunological phenotype of circulating T cells and M-MDSCs: original research - Lepper, Alisa; Bitsch, Rebekka; Özbay Kurt, Feyza Gül; Arkhypov, Ihor; Lasser, Samantha; Utikal, Jochen; Umansky, Viktor (OncoImmunology, 2023)
Treatment with immune checkpoint inhibitors (ICIs) has improved the prognosis of melanoma patients. However, ICIs can cause an overactivation of the immune system followed by diverse immunological side effects known as immune-related adverse events (irAE). Currently, the toxicity of irAE is limiting the usage of ICIs. Here, we studied circulating monocytic myeloid-derived suppressor cells (M-MDSCs) and T cells in course of irAE after the ICI therapy. Our longitudinal study involved 31 melanoma patients with and without adverse events during anti-PD-1 monotherapy or anti-CTLA-4/PD-1 combination therapy. Peripheral blood samples were analyzed before ICI start, during ICI treatment, at the time point of irAE and during immunosuppressive treatment to cure irAE. We observed an enhanced progression-free survival among patients with irAE. In patients with irAE, we found an upregulation of CD69 on CD8+ T cells and a decreased frequency of regulatory T cells (Tregs). Moreover, lower frequencies of Tregs correlated with more severe side effects. Patients treated with immunomodulatory drugs after irAE manifestation tend to show an elevated number of M-MDSCs during an immunosuppressive therapy. We suggest that an activation of CD8+ T cells and the reduction of Treg frequencies could be responsible for the development of irAE.
Gesehen am 16.04.2024